2018
DOI: 10.1155/2018/5072582
|View full text |Cite
|
Sign up to set email alerts
|

Update on Vertigo in Autoimmune Disorders, from Diagnosis to Treatment

Abstract: The prevalence of autoimmune diseases has been increasing over the last 20 years. The clinical presentation of this large and heterogeneous group of disorders depends on whether the involvement is organ-specific or non-organ-specific. Dizziness, vertigo, and disequilibrium are common symptoms reported by patients with vestibulocochlear involvement. The association of vertigo and autoimmune diseases has been largely documented, suggesting that autoimmune disorders could be overrepresented in patients with verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 161 publications
1
38
0
13
Order By: Relevance
“…gentamicin, furosemide) [39,40]. In the 1990s, an autoimmune basis of the disease was suspected [41][42][43][44][45]. The condition is manifested by sudden, severe vertigo (spinning sensation), resulting from sudden unilateral weakness or loss of labyrinth function.…”
Section: Vestibular Neuritismentioning
confidence: 99%
See 3 more Smart Citations
“…gentamicin, furosemide) [39,40]. In the 1990s, an autoimmune basis of the disease was suspected [41][42][43][44][45]. The condition is manifested by sudden, severe vertigo (spinning sensation), resulting from sudden unilateral weakness or loss of labyrinth function.…”
Section: Vestibular Neuritismentioning
confidence: 99%
“…Although almost every patient who is hospitalised due to vestibular neuritis is routinely assessed for thyroid disorders, to the best of our knowledge, there are no objective study results that could confirm the relationship between these two diseases. According to Girasoli et al, immune-mediated vestibular disorders are rare and difficult to diagnose [43]. Those authors emphasised the lack of objective tests to confirm immune processes that occur in the structures of the inner ear, which could directly contribute to vertigo.…”
Section: Vestibular Neuritismentioning
confidence: 99%
See 2 more Smart Citations
“…Ménière's disease (MD) is a multifactorial disorder of the inner ear characterized by vertigo, tinnitus, and sensorineural hearing loss [Girasoli et al, 2018]. MD is characterized by fluctuating symptoms and episodic attacks, and it has been suggested that dietary components and stress are associated with MD attacks and symptom spikes [Kirby and Yardley, 2012].…”
Section: Introductionmentioning
confidence: 99%